2021
DOI: 10.3390/en14237927
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Thermally Activated Building System with Horizontal Ground Heat Exchanger Considering the Weather Conditions

Abstract: The thermally activated building system (TABS) can reduce the peak load by integrating with the ground heat exchangers. When integrated, the cost of groundwork and stability of the ground temperature would counteract because the weather conditions would influence the ground temperature in shallow depth. However, previous studies on TABS assumed constant ground temperatures such as average outdoor air temperature. In this study, ground temperatures in different depths are simulated for their detailed investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Physical processes and soil properties can account for the increase in soil thermal damping with depth. The heat transfer rate diminishes with the soil depth, leading to less influence from external temperature variations [61].…”
Section: Discussionmentioning
confidence: 99%
“…Physical processes and soil properties can account for the increase in soil thermal damping with depth. The heat transfer rate diminishes with the soil depth, leading to less influence from external temperature variations [61].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was established that the temperature differential between the inside environment and the roof ranged from 5°C to 7°C. Chung and Park (2021) provide simulation research designed to evaluate a structure with TABS integrated into the roof. According to Chung et al, the thermal comfort increased by 5% when the proposed building was divided into zones with various control strategies based on the requirements of each floor.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to apply mathematical modelling for this purpose, as it allows for specification of the time needed for thermal regeneration of the ground after the heating season, among other functions. Despite the existence of natural thermal regeneration in the summer season, too much intensive exploitation of a heat exchanger during the heating season can cause excessive cooling of the ground [9,10]. In [2], it was found that during the winter season, the gravel heat exchangers can be used to provide about 50% of the heat for ventilation, and during the summer season to meet up to 100% of demand for building cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations carried out in [9][10][11] show that the ground thermal conductivity significantly affected the value of the minimum temperature occurring at a given depth of the heat exchanger's installation. Therefore, the ground heat exchanger will be best protected against the occurrence of excessively low temperatures if it is installed in-ground with high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%